Factors related to Acceptance of HIV Testing by Pregnant Mothers in Health Centres in Denpasar City - Ni Ketut Arniti; Luh Putu Wulandari; Dewa Nyoman Wirawan (Public Health and Preventive Medicine Archive, 2014)
Purpose: To determine reasons of pregnant mothers to undergo HIV testing and factors influencing this decision. Methods: The study design was a cross-sectional survey with a sample of 120 pregnant mothers seeking antenatal care in two sites: Puskesmas I Denpasar Utara and Puskesmas II Denpasar Selatan, during the period of 26 March to 22 April 2014. Data were collected through interviews using a structured questionnaire. Data were analysed using univariate to determine the frequency distribution of each variable, bivariate to determine the relationship between the dependent variable with each independent variable by the chi-squared test and multivariate analysis performed by logistic regression to determine the dominant factors to improve the acceptance of pregnant mothers to HIV testing. Results: Reasons to undergo HIV testing were on recommendation from health providers (65.8%), concern for personal status (61.7%) and concerns about possibility of vertical transmission (19.2%). Bivariate analysis showed that the acceptance by pregnant mothers was higher in mothers unemployed (75.8%; p=0.033), good knowledge about HIV and its transmission (78.4%; p=0.001), was susceptible to HIV/AIDS (72.0%; p=0.019), the perception that HIV/AIDS is a severe disease (77.0%; p≤0.001), perceptions of the benefits of HIV testing (70.8%; p=0.002), absence perceived barriers (100%; p≤0.001) as well as good support from husband/family (87.7%; p≤0.001). Multivariate analysis showed that factors influencing were support from husband/family with OR=8.71 (95%CI: 2.89-26.28), perception of severity of HIV with OR=3.39 (95%CI: 1.08-10.69) and employment status with OR=2.82 (95%CI: 1.07-7.42). Conclusion: The majority of women to undergo HIV testing because of recommendations by staff and a desire to know HIV status. Acceptance of HIV testing among pregnant mothers was influenced by the support of the husband/family, the perception of the severity of HIV / AIDS, and employment status.